International bank settlement in China and unilateral sanctions-related disputes: sources, remedies and procedures - Sun, Jin (Research Handbooks in International Law series, 2021)
Through fieldwork investigations and a review of judicial cases, this chapter completes the first empirical research of unilateral extraterritorial sanctions in Mainland China, Hong Kong and Macao. It shows how they are different from the US and EU with regard to sources, remedies and procedures. In China, remedies take many forms in practice, not limited to judicial remedies. Local banks and individuals favour administrative, not judicial, remedies. In judicial litigation, to unfreeze money under unilateral sanctions or to settle disputes of international payment, it is not necessary to file a legal review and annul sanctions decision as in the EU. In China, with unilateral sanctions not recognized in court, it could be simplified as a request to honour the payment. Chinese offshore banking practices in Hong Kong and Macao, the legal orders are the opposite: they officially recognize and enforce unilateral US and EU sanctions.